Regulatory mechanisms in coastal zone management: the coastline setback policy in Barbados. The Journal of the Barbados Museum and Historical Society. Vol.39, p.72-80. - Atherley, K.A. and Nurse, L.A. (2011)
The deterioration of the Barbados coast is a result of combined human and natural factors. The coastline setback policy, in place for almost 20 years, is used as one of the key instruments of development, control and coastal conservation.